INNOVATIVE APPROACHES TO TEACHING ANALYTICAL GEOMETRY WITH THE HELP OF MODERN PEDAGOGICAL TECHNOLOGIES - Jamshid Ozodovich Xasanov (European Science Publishing, 2024)
In this article innovative apptoaches to teaching analytical geometry, aimed at the perception and assimilation of students of complex mathematical concepts are considered. Also presented the benefits of using pedagogical technologies such as interactive platforms, blended learning and project methods, including practical recommendations on successful application of modern technologies in the educational process to increase students` interest and participation in this science.
Keywords: Innovative technologies, pedagogical technologies, analytical geometry, interactive learning, visualization in learning, gamification, blended learning, digital platforms, higher education, mathematical education.